Analysis of pest risk for Ukraine Cydia inopinata Heinrich - L. Titova; Y. Klechkovskiy; O. Palagina (Карантин і захист рослин)
Goal. Carrying-out of a pest risk analysis (PRA) for Ukraine in relation to Cydia inopinata Heinrich (Manchurian moth) — pest of fruit and ornamental crops, according to the EPPO standard PM 5/3 (5) and improvement of methods for assessing the probability of acclimatization of adventive pest organisms beyond existing areas using modern computer software.